Carbon capture in laval nozzles with different bicubic parametric curves and translation of witoszynski curves. (1st December 2022) - Chen, Jianan; Huang, Zhu; Li, Anna; Gao, Ran; Jiang, Wenming
Abstract: This work investigates the influence of convergent curve of supersonic nozzle on the carbon separation process. The CFD model based on nucleation and growth theory, second-order upwind scheme and density-based solution method are employed to predict the CO2 supersonic separation process in the nozzle. The effects of bicubic parametric curve and translation of Witoszynski curve on flow characteristics and spontaneous condensation characteristics are illustrated. The results show that the mixed gas accelerates and deviates from the equilibrium state in the Laval nozzle, and nucleation occurs when the supersaturation is greater than 1.81. After nucleation, gas enters the droplet growth stage, during which mass and heat transfer are carried out between gas and liquid phase, and the droplet radius increases continuously. With the increase of the parameter x m in the bicubic parametric curve equation and the axis shift quantity y h in the translation of Witoszynski curve equation, the flow parameters in the nozzle change more violently, the nucleation location moves to the nozzle exit, and the interphase mass transfer rate and liquid fraction decrease in varying degrees. Highlights: Proposing a CFD model for calculating spontaneous condensation of CO2 in flue gas. A clean and energy-saving potential carbon separation method. Optimizing convergent curve based on condensation model. Moving the connection point forward is beneficial to CO2 separation. Reducing axis shift quantity is beneficial to CO2 separation.